2015
DOI: 10.1088/0031-9155/60/7/2765
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated gradient-based free form deformable registration for online adaptive radiotherapy

Abstract: The registration of planning fan-beam computed tomography (FBCT) and daily cone-beam CT (CBCT) is a crucial step in adaptive radiation therapy. The current intensity-based registration algorithms, such as Demons, may fail when they are used to register FBCT and CBCT, because the CT numbers in CBCT cannot exactly correspond to the electron densities. In this paper, we investigated the effects of CBCT intensity inaccuracy on the registration accuracy and developed an accurate gradient-based free form deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…We found that intensity‐based deformable registration algorithms are susceptible to distorting tissues because the presence of inconsistent intensities between CT and CBCT could cause significant registration errors. The DIR algorithm performed in this study was presented in our previous work, and was tested using phantom and clinical data, which demonstrated the significance of the registration method 23. We assessed the volume overlapping using the Dice Similarly coefficient (DSC) in that study.…”
Section: Discussionmentioning
confidence: 99%
“…We found that intensity‐based deformable registration algorithms are susceptible to distorting tissues because the presence of inconsistent intensities between CT and CBCT could cause significant registration errors. The DIR algorithm performed in this study was presented in our previous work, and was tested using phantom and clinical data, which demonstrated the significance of the registration method 23. We assessed the volume overlapping using the Dice Similarly coefficient (DSC) in that study.…”
Section: Discussionmentioning
confidence: 99%
“…The abdominal phantom (1), bolstered by a vacuum bag (5), was equipped with four connected blood pressure cuffs (2) with an inflation bulb (3), and an aneroid gauge (4), which were used to generate compression force to induce deformation. The frame (6) was used to support the ionization chamber cables (7) During deformable gel preparation, continuously stirring of the heated mixture of PVC and softener was important to avoid air bubbles trapped in the molten gel. It would be beneficial to place the polymerized gel inside a vacuum chamber for 1~2 min to induce a boiling effect by pressure change and the air bubbles will disappear upon pressure release.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, many efforts have been made in developing novel DIR approaches with applications in ART . Yet, a more urgent question we need to answer is how to assess the uncertainty or validate the accuracy of these existing DIR approaches in the context of ART.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications include multimodality image registration, (1) atlas‐based automatic segmentation, (2) dose summation, (3) and contour propagation for online, 4 , 5 and offline 4 , 6 adaptive radiation therapy. Unlike conventional “rigid” registration, DIR does not assume spatial invariance between all voxels of both image sets.…”
Section: Introductionmentioning
confidence: 99%